Moral Contingency and Moral Supervenience - Bedke, Matthew S. (Journal of moral philosophy, 2025)
Moral Supervenience says that there can be no moral difference without a descriptive difference. This has been considered one of the least controversial principles in ethics. Explaining it has been a central desideratum. And yet an increasingly popular metaethical view appears to be incompatible with it. According to Moral Contingency, there are metaphysically contingent pure moral principles helping to ground particular moral facts. On such a view, it looks like there can be a difference in pure moral principles without a descriptive difference. This looks like a moral difference without a descriptive difference. Are those who find both Moral Supervenience and Moral Contingency plausible faced with a difficult choice? Many contingentists think so, but I am here to argue that they are mistaken. The two principles are compatible after all, for differences in pure moral principle entail descriptive differences.